2019
DOI: 10.5539/elt.v12n5p177
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies (VLSs) Employed by Learners of English as a Foreign Language (EFL)

Abstract: Learning a new language entails various challenges, one of these is grasping the vocabulary of the language. A significant way to tackle the problem is to motivate students to become independent learners during the progression of second language (L2) vocabulary learning. Thus, this study intended to explore the use of different vocabulary learning strategies among adult English as foreign language learners and investigated the various vocabulary learning strategies and found the benefits and drawbacks associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 7 publications
(14 reference statements)
2
25
0
Order By: Relevance
“…The ESL teachers should demonstrate the proper learning strategies in order to relieve the current pressure among the ESL learners. There are varieties of vocabulary learning strategies could be employed by learners such as determination strategies, memory strategies, cognitive strategies, metacognitive strategies, social strategies established throughout the devised taxonomy from Schmitt (1977) cited in Goundar (2019). Nonetheless, Yaacob et al (2019) highlighted LLSs could be another important tool in acquiring vocabulary as LLSs are the onset of the vocabulary learning strategies.…”
Section: Vocabulary Learning In Eslmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESL teachers should demonstrate the proper learning strategies in order to relieve the current pressure among the ESL learners. There are varieties of vocabulary learning strategies could be employed by learners such as determination strategies, memory strategies, cognitive strategies, metacognitive strategies, social strategies established throughout the devised taxonomy from Schmitt (1977) cited in Goundar (2019). Nonetheless, Yaacob et al (2019) highlighted LLSs could be another important tool in acquiring vocabulary as LLSs are the onset of the vocabulary learning strategies.…”
Section: Vocabulary Learning In Eslmentioning
confidence: 99%
“…Cognitive strategies compromise the process from mental relation to the information input through applying, acquiring, processing, remembering and using the information directly. Goundar (2019) postulated the learners who executed cognitive strategies would be able to guess the words by drawing upon of the prior knowledge and utilizing the linguistic clues and grammatical structures of a sentence to derive the meaning of the word. In order word, cognitive strategies highly implemented guessing strategy due to the processes undergo the mental and link to the background knowledge to progress the meaning.…”
Section: Vocabulary Learning In Eslmentioning
confidence: 99%
“…Similarly, the learners may apply activation strategies that involve different tactics such as to practise the new words in different contexts. These strategies can work in addition to other essential learning strategies such as metacognitive strategies, cognitive, memory and others (Goundar, 2016). Figure 1 illustrates that PSAU students also faced problems in "Using New Vocabulary in Speaking or Writing".…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have looked into the uses of different VLS by ESL learners within the online gaming platform. Also using Gu and Johnson's (1996) Categorisation of VLS, Goundar (2019) examined the different strategies that were employed by English as a Foreign Language (EFL) learners in learning new English vocabulary. Goundar (2019) found that participants employed a number of VLSs in order to acquire vocabulary and strategies that enhanced their memory-retaining skill.…”
Section: Figurementioning
confidence: 99%
“…Also using Gu and Johnson's (1996) Categorisation of VLS, Goundar (2019) examined the different strategies that were employed by English as a Foreign Language (EFL) learners in learning new English vocabulary. Goundar (2019) found that participants employed a number of VLSs in order to acquire vocabulary and strategies that enhanced their memory-retaining skill. They also shed light on the effectiveness of VLS as a tool in describing and explaining EFL learners' language development, in addition to its capability in empowering students to choose which VLS that they require to use in order to acquire new vocabulary (Gu, 2003, as cited in Goundar, 2019.…”
Section: Figurementioning
confidence: 99%